Balloon occlusion of the carotid artery prior to surgery for neck tumors. - Gonzalez, C F; Moret, J (American Journal of Neuroradiology, 1990)
We present the results of presurgical balloon occlusion of the carotid artery in 22 patients with cervical lymphadenopathy stage N3. The procedure was found to be extremely useful in preventing rupture of the carotid artery, considered the most dangerous complication of neck cancer surgery. Complications of the balloon procedure were few (10%) when compared with surgical ligation of the carotid artery (41-54% stroke frequency and 32-60% mortality). This procedure also allows testing of the collateral circulation before final detachment of the balloon, a maneuver that prevents stroke in many patients.